2002
DOI: 10.1089/08977150252932415
|View full text |Cite
|
Sign up to set email alerts
|

Release of Excitatory Amino Acids in the Penumbra of a Focal Cortical Necrosis

Abstract: A cortical tissue necrosis from focal trauma expands between 30% and 300% from its initial size within 24 h, depending on the species studied. To shed light on the pathophysiological processes in the penumbra 1 zone after a focal cortical lesion, the release of excitatory amino acids into the traumatic penumbra zone 1 was measured throughout the entire period of necrosis expansion. A microdialysis probe was inserted at an oblique angle into the cortex of Sprague-Dawley rats 2 mm below the brain surface. One da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The time point of 90 minute after CHI was chosen because previous studies have demonstrated that the excess glutamate concentration in brain fluids in the rat model of CHI reaches a peak after about 1 hour. 12,13,29,30 MAP, HR, arterial blood gas tensions, and Hb concentrations were assessed at 0, 60, 90, and 120 minutes after closed head injury. The MAP was lower in the maleate group compared with the saline treatment group at 90 minutes (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The time point of 90 minute after CHI was chosen because previous studies have demonstrated that the excess glutamate concentration in brain fluids in the rat model of CHI reaches a peak after about 1 hour. 12,13,29,30 MAP, HR, arterial blood gas tensions, and Hb concentrations were assessed at 0, 60, 90, and 120 minutes after closed head injury. The MAP was lower in the maleate group compared with the saline treatment group at 90 minutes (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The surrounding neural tissue suffers from the secondary effects characterized by apoptosis (Guyot et al 2001; Stoffel et al 2002). A critical determinant of cell death in the penumbra is thought to be excessive release of glutamate from injured cells and the attendant glutamate-dependent excitotoxicity of “bystander” cells (Arundine and Tymianski 2004; Choi 1988; Hazell 2007).…”
Section: Modified Model For Mechanisms Of Glutamate-dependent Excitotmentioning
confidence: 99%
“…Nowadays, it is well accepted that abnormally high Glu levels in brain interstitial and cerebrospinal fluids are the hallmark of several neurodegenerative conditions, such as stroke and, traumatic brain injury (Castillo et al 1996;Johnston et al 2001;Stoffel et al 2002;Suzuki et al 2002). As excess Glu exerts neurotoxic properties, a great deal of efforts has been made in recent years to reach a better understanding of how the brain protects itself from excess Glu, and on ways drugs could provide neuroprotection.…”
Section: Discussionmentioning
confidence: 99%